2001
DOI: 10.1515/prbs.2001.004
|View full text |Cite
|
Sign up to set email alerts
|

Focus and early peak alignment in Spanish intonation

Abstract: Recent work on Spanish intonation has shown that words in narrow focus often have an F0 peak within the stressed syllable, while when not in focus the peak generally follows the stressed syllable. Agreement has not been reached, however, as to an appropriate phonological analysis of this intonation pattern. It is shown here that this early F0 peak is the result of a focal pitch accent rather than the phonetic effect of a following intermediate phrase boundary. In addition, it is shown that this is not the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 3 publications
(13 reference statements)
3
72
3
4
Order By: Relevance
“…These results suggest that pitch categories alone cannot account for the realization of focus in Asturian Spanish, as opposed to what other studies have shown for other dialects of Peninsular Spanish (Face 2001;Nibert 2000;Vanrell and Fernández-Soriano in press), at least in the type of situations used in this experimental task to elicit informational focus. Interestingly, the configuration reported in some of the previous studies, that is, L+H* followed by a falling intermediate boundary tone (L-), was found most consistently in the speech of the participant who acknowledged the lower degree of influence of Asturian in his Spanish.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…These results suggest that pitch categories alone cannot account for the realization of focus in Asturian Spanish, as opposed to what other studies have shown for other dialects of Peninsular Spanish (Face 2001;Nibert 2000;Vanrell and Fernández-Soriano in press), at least in the type of situations used in this experimental task to elicit informational focus. Interestingly, the configuration reported in some of the previous studies, that is, L+H* followed by a falling intermediate boundary tone (L-), was found most consistently in the speech of the participant who acknowledged the lower degree of influence of Asturian in his Spanish.…”
Section: Discussioncontrasting
confidence: 97%
“…The use of the focal pitch accent L+H* found in other dialects of Spanish (Face 2001;Face and Prieto 2007;Vanrell and Fernández-Soriano in press) did not increase significantly enough to confirm its phonological role among the group of participants of this study, and it was only present in the speech of a few participants. This provides support to the idea of an underlying rising pitch accent (LH)* proposed in Hualde (2002).…”
Section: )contrasting
confidence: 52%
See 1 more Smart Citation
“…In addition, most of the work concentrates on declarative modality, particularly on the expression of focus. Although we find exceptions (such as Zubizarreta 1998 andGabriel 2010 for Spanish), there is often a stark division between those studies that emphasize the syntactic perspective (syntactic mechanisms to mark focus : Solà 1990, Vallduví 1991Costa 2001, Gutiérrez-Bravo 2002, 2005, Domínguez 2004, Samek-Lodovici 2001, 2005 among others for Spanish) and those that draw attention to the prosodic perspective (description of the focal shape and the use of different prosodic parameters such as duration, and peak alignment/scaling: Estebas-Vilaplana 2000, Prieto in press-2014, Vanrell et al 2013 for Catalan;de la Mota 1995, Sosa 1999, Face 2001, Hualde 2002, 2005, Gabriel 2006, 2007, Vanrell et al 2013 for Spanish). The few studies addressing interrogative modality mainly concentrate on word order and tend to disregard dialectal variation (an exception is Prieto and Rigau 2007 for Catalan).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from in isolated words, the peak is not delayed when the word is under narrow focus (Face 2001), and strict alignment is the norm in the speech of Buenos Aires and its area of influence, which extends to Uruguay (Sosa 1999).…”
Section: Stress Cues In Spanishmentioning
confidence: 99%